A Self-Calibration Method of Zooming Camera - El Batteoui, Ismail; Saaidi, Abderrahim; Satori, Khalid (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
In this article we proposed a novel approach to self- calibrate a camera with variable focal length. We show that the estimation of camera’s intrinsic parameters is possible from only two points of an unknown planar scene. The projection of these points by using the projection matrices in two images only permit us to obtain a system of equations according to the camera’s intrinsic parameters . From this system we formulated a nonlinear cost function which its minimization allows us to estimate the camera’s intrinsic parameters in each view. The results on synthetic and real data justify the robustness of our method in term of reliability and convergence.
Keywords: focal length; nonlinear cost function; projection matrices; zoom camera; IJIMAI